Anti-EGFR Therapy: Mechanism and Advances in Clinical Efficacy in Breast Cancer. (14th April 2009) - Flynn, John F.; Wong, Christina; Wu, Joseph M.
Abstract : This review will focus on recent advances in the application of antiepidermal growth factor receptor (anti-EGFR) for the treatment of breast cancer. The choice of EGFR, a member of the ErbB tyrosine kinase receptor family, stems from evidence pinpointing its role in various anti-EGFR therapies. Therefore, an increase in our understanding of EGFR mechanism and signaling might reveal novel targets amenable to intervention in the clinic. This knowledge base might also improve existing medical treatment options and identify research gaps in the design of new therapeutic agents. While the approved use of drugs like the dual kinase inhibitor Lapatinib represents significant advances in the clinical management of breast cancer, confirmatory studies must be considered to foster the use of anti-EGFR therapies including safety, pharmacokinetics, and clinical efficacy.